Simulating the evolution of the chemical composition of the 1988/89 winter vortex - Jones, R. L.; Mckenna, D. S.; Poole, L. R.; Solomon, S. (1990)
During the 1988/89 Airborne Arctic Stratospheric Expedition (AASE) observations of the chemical composition and aerosol characteristics of the winter vortex were obtained from a NASA ER-2 aircraft. In this paper we present interpretations of observations obtained on three ER-2 flights using a Lagrangian coupled photochemical-microphysical model. It is argued that observations obtained on Jaunary 16 and 19, and February 10, represent different stages of the chemical evolution of the vortex, from the early stages of chlorine release, the onset of denitrification and the intensively processed state.